(untitled) (Agricultural Engineering, 2018)
The paper presents results of analysis of turbidity changes in washing solutions and the quantity of solid particles present in them during regeneration under various temperature conditions. Three solutions taken from breweries after the process of washing brewhouse equipment in the CIP system were evaluated. The results were subjected to statistical analysis, to define the functions that characterize the changes of the tested parameters in relation to time and temperature. The results showed that the tested solutions have different favourable conditions for their regeneration. It has also been shown that the character of changes in solutions in the regeneration process is more advantageously determined on the basis of turbidity tests of solutions.